Agency and the feminist debate on the abolition, legalization, or decriminalization of sex work: voices from the advocates - Durham, Lori A. (2015)
Although sex work is considered the oldest profession it is possibly more controversial today than any other time in history. Divisions exist in feminists’ philosophy regarding sex work, particularly around the issue of personal agency. Feminists, typically, embrace one of three positions – abolition, legalization with regulations, or decriminalization. Most academic literature fails to include the perspective of sex workers when debating the legality and practicality of sex work. The purpose of this research is to gain insight into the reasons individuals become involved in sex work, including agency, through stories shared with third-party professionals and advocates; inquire whether sex workers would remain in or leave the industry if other opportunities were available; and explore the consequences of sex work laws